2003
DOI: 10.1161/01.cir.0000047210.07839.7b
|View full text |Cite
|
Sign up to set email alerts
|

Beating Atrial Septal Defect Closure Monitored by Epicardial Real-Time Three-Dimensional Echocardiography Without Cardiopulmonary Bypass

Abstract: Background-We assessed the feasibility of beating atrial septal defect (ASD) closure monitored by real-time 3D echocardiography (RT3DE). Methods and Results-RT3DE was developed with prototype ultrasound equipment consisting of a high-speed 3D rendering unit with a frame rate of 5 to 10 frames/s. We also developed a prototype semiautomatic suture device and suture cutting system. In the experiment, 12 mongrel dogs were anesthetized, and after median sternotomy, the echo probe was applied directly to the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…The use of epicardial 3DE via a rotational transducer and volume mode imaging has been demonstrated in assisting in the surgical closure of atrial septal defects off cardiopulmonary bypass in dogs. 22 In adult humans undergoing Amplatzer device occlusion of ASD, transesophageal 3DE image rendering (with postprocessing) has been shown to allow for superior delineation of ASD morphology when compared to transesophageal 2DE images. 23 (with postprocessing) was shown to be comparable to 2D TEE in determining maximal ASD diameter in patients undergoing device closure of their defects.…”
Section: Discussionmentioning
confidence: 99%
“…The use of epicardial 3DE via a rotational transducer and volume mode imaging has been demonstrated in assisting in the surgical closure of atrial septal defects off cardiopulmonary bypass in dogs. 22 In adult humans undergoing Amplatzer device occlusion of ASD, transesophageal 3DE image rendering (with postprocessing) has been shown to allow for superior delineation of ASD morphology when compared to transesophageal 2DE images. 23 (with postprocessing) was shown to be comparable to 2D TEE in determining maximal ASD diameter in patients undergoing device closure of their defects.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of minimally invasive surgery is expanding, it includes not only cosmetic approach, but also beating heart surgery avoiding cardioplegia, port access to avoid sternotomy and recently experiments are underway using robotic technique under real time echocardiographic guidance to repair intracardiac defects completely avoiding cardiopulmonary bypass 13,14 .…”
Section: Safety and Efficacy Of Atrial Septal Defect Closure On Normomentioning
confidence: 99%
“…The development of new surgical procedures in the future should enable operations like ASD occlusion or mitral valve repair on the beating heart under 3D echocardiographic control. Suematsu et al (15)(16)(17)(18) have demonstrated the feasibility of such procedures in their latest studies, whereby they performed the studies on the model with transthoracic RT3DE systems. As the authors noted, RT3D-TEE would be necessary for clinical applications.…”
Section: Perspectives and Clinical Implications Of Rt3d-teementioning
confidence: 99%